Tax Evasion between Fraud and Legality (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
This paper focuses on detailing the general coordinates regarding tax evasion and the necessity of creating a common unitary European legal framework. Accounting information might mirror erroneously in a certain measure the micro to macroeconomic tendency of fraud by showing a gross image of available resources. It is of the utmost importance to become fully aware of causes for illicit practices, ways to fight any fraud attempts and to evaluate the accounting mechanism that both creates and identifies tax evasion.